2017
DOI: 10.3389/fmicb.2017.01295
|View full text |Cite
|
Sign up to set email alerts
|

Anti-adhesion and Anti-biofilm Potential of Organosilane Nanoparticles against Foodborne Pathogens

Abstract: Nowadays, modification of surfaces by nanoparticulate coatings is a simple process that may have applications in reducing the prevalence of bacterial cells both on medical devices and food processing surfaces. To this direction, biofilm biological cycle of Salmonella Typhimurium, Listeria monocytogenes, Escherichia coli O157:H7, Staphylococcus aureus, and Yersinia enterocolitica on stainless steel and glass surfaces, with or without nanocoating was monitored. To achieve this, four different commercial nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 59 publications
(65 reference statements)
2
12
0
Order By: Relevance
“…Moreover, Al 2 O 3 -NPs were more active against B. cereus and S. aureus than S. typhimurium, the results were partially agreement with the author [25]. In addition, SiO 2 -NPs were more active against B. cereus, and S. typhimurium compared S. aureus that is not it at all by Gkana et al [26]. The results indicated that the Al 2 O 3 -NPs were more active against spores and gram-positive than gram-negative bacteria, while SiO 2 -NPs more effective against gramnegative and spores compared with grampositive bacteria.…”
Section: Antimicrobial Activity Of Nanoparticles Against Foodborne Pasupporting
confidence: 81%
“…Moreover, Al 2 O 3 -NPs were more active against B. cereus and S. aureus than S. typhimurium, the results were partially agreement with the author [25]. In addition, SiO 2 -NPs were more active against B. cereus, and S. typhimurium compared S. aureus that is not it at all by Gkana et al [26]. The results indicated that the Al 2 O 3 -NPs were more active against spores and gram-positive than gram-negative bacteria, while SiO 2 -NPs more effective against gramnegative and spores compared with grampositive bacteria.…”
Section: Antimicrobial Activity Of Nanoparticles Against Foodborne Pasupporting
confidence: 81%
“…27 Moreover, nanoparticles of iron oxide, tin oxide, gold, copper and organosilane have also been shown to inhibit biolm of L. monocytogenes. [42][43][44][45][46] This is probably the rst report on the inhibition of biolm formation in Listeria species by green synthesized AgNPs.…”
Section: Effect On Biolm Formationmentioning
confidence: 77%
“…More specifically, in the case of glass surface the attached and biofilm cell population of different enteropathogenic strains was found to be lower than on stainless steel surface (Gkana et al, 2017). Stepanović et al 2004 (Table 2).…”
Section: Accepted Manuscriptmentioning
confidence: 93%